Respuesta :
Answer:
2
Step-by-step explanation:
9x + 9 = 25 + x
8x = 16
x = 2
make sure to ask if you need any further guidance.
Answer: A) x = 2
Step-by-Step Explanation:
9(x + 1) = 25 + x
9 * x + 9 * 1 = 25 + x
9x + 9 = 25 + x (Shift +x to LHS)
9x - x + 9 = 25 (Shift +9 to RHS)
9x - x = 25 - 9
8x = 25 - 9
8x = 16 (Shift *8 to RHS)
x = 16/8
=> x = 2
Therefore, x = 2
Step-by-Step Explanation:
9(x + 1) = 25 + x
9 * x + 9 * 1 = 25 + x
9x + 9 = 25 + x (Shift +x to LHS)
9x - x + 9 = 25 (Shift +9 to RHS)
9x - x = 25 - 9
8x = 25 - 9
8x = 16 (Shift *8 to RHS)
x = 16/8
=> x = 2
Therefore, x = 2